Transformasi Digital UMKM Sari Nabati Kudus: Pelatihan dan Pendampingan Marketplace Berbasis Platform E-Commerce - Tri Listyorini; Endang Supriyati; Mohammad Iqbal (Pusat Penelitian dan Pengabdian Masyarakat, 2026)
The development of digital technology has opened great opportunities for micro, small, and medium enterprises (MSMEs) to expand their market reach through marketplace platforms. However, many MSME actors in Kudus, especially plant-based beverage producers, still face obstacles in optimally utilizing online platforms. This community service activity aims to increase the capacity of plant-based beverage MSME actors in Kudus in conducting online sales through marketplace-based training and mentoring. The service partners are a group of plant-based beverage producer MSMEs in Kudus, totaling 25 business actors. The methods used include training in online store management, product photography, stock management, digital marketing strategies, and intensive mentoring for three months. The results showed a significant increase in participants' knowledge and skills, with an average post-test score 65% higher than the pre-test. As many as 80% of participants successfully opened online stores on marketplaces such as Shopee, Tokopedia, and Bukalapak. Average sales turnover increased by 45% in the first three months after training. In conclusion, the marketplace-based training and mentoring program has proven effective in increasing the capabilities and sales performance of plant-based beverage MSMEs in Kudus.